PENGARUH ORIENTASI PELANGGAN, PENJUALAN ADAPTIF, DAN KUALITAS HUBUNGAN TENAGA PENJUAL-PELANGGAN TERHADAP KINERJA TENAGA PENJUAL - Hendra Saputra; Diana Aqmala (Politeknik Ubaya, 2018)
Intense competition between companies in the era of a global economy requires companies to always be the leader and best in providing satisfactory service to consumers especially companies engaged in services. Sales force management is often seen as part of marketing management is crucial in supporting the success of the company. The purpose of this study to analyze the impact of customer orientation, adaptive selling, and quality-customer relationship salesperson to salesperson performance. Methods in this study conducted by questionnaire. The population in this study is the salesperson who is in the marketing office of PT. Prudential Life Assurance in JL Dr. Cipto Mangunkusumo, No. 40 A Semarang, the sample used in this study were 85 respondents and sampling of the population using purposive sampling technique. Testing the hypothesis in this study using multiple regression analysis with SPSS applications 21. The results of the study with multiple linear regression showed that adaptive selling and quality of the salesperson-customer relationship positive and significant effect on salespeople performance, and customer orientation does not affect the salespeople performance.